Rice Bran Quality Based on Physical Properties and Chemical Composition Estimation in Maros Regency, South Sulawesi - Muhammad Ridla; Firdayanti Firdayanti; Erica B. Laconi; Nevyani Asikin (Faculty of Animal Science, Universitas Brawijaya, 2023)
Rice bran, a byproduct generated during the rice milling process, is widely utilized as a livestock feed ingredient. However, the quality of rice bran can vary across different production regions. This study aimed to evaluate the quality of rice bran in Maros District, South Sulawesi, Indonesia, based on its physical properties and predicted nutrient contents. The study employed a completely randomized design, with ten treatments (representing rice mills from Bonto Marannu, Maccini Baji, Allepolea, Majannang, Salenrang, Turikale, Allatengae, Soreang, Baju Bodoa, and Tunikamaseang) and four replications. The data were analyzed using analysis of variance (ANOVA) and Duncan's multiple range test. The results revealed a highly significant effect (P<0.01) of the rice mill location on the physical quality and predicted nutrient contents of rice bran. The bulk density and tapped density densities varied (P<0.01) among the ten rice mills located in five sub-districts of Maros District, while the predicted crude protein and crude fiber contents also showed variation (P<0.01). The highest values were observed in the rice bran from the Allatengae mill, while the lowest values were found in the rice bran from the Allepolea mill. In this study, the quality of rice bran was categorized into grades I, II, and III according to Standard Nasional Indonesia (2013), based on its physical quality and predicted nutrient contents